Recent trends in the pattern and long-term management strategy of patients diagnosed with acute coronary syndrome in India: an observational study - Nayak, Mithilesh; Patel, Dixit; Chaturvedi, Alok; Shah, Ankita (International Journal of Research in Medical Sciences, 2022)
Background: The understanding of demographic patterns and the real-world management practices for patients with acute coronary syndrome (ACS) will facilitate optimizing the management strategies for ACS based on the patient’s clinical profile and the associated risk factors in Indian patients. Hence, this study determined the demographic details and the treatment patterns in Indian patients with ACS. Methods: The RECent trends in the pattern and lOng-term management stRategy of patients Diagnosed with acute coronary syndrome in India (RECORD ACS-2) study was a real-world, retrospective, cross-sectional, observational study conducted at various centres across India between 2021 and 2022. The study outcomes included the demographic profile and therapeutic management in patients with ACS. Results: A total of 9945 patients with a mean age of 59 years were included. The ACS was commonly observed in the age group of 41-70 years with highest incidence in the age group of 51-60 years. The ST-elevation myocardial infarction (STEMI) was most common (53.2%) presentation. Hypertension (37.2%) and dyslipidemia (29.3%) followed by diabetes (21.3%) were the most common comorbidities. Single vessel disease was the most common angiographic feature (58%). Percutaneous coronary intervention was the most preferred management strategy (57%). Ticagrelor was the most preferred loading (68.3%) as well as maintenance (71.2%) P2Y12 inhibitor in ACS patients. Most of the patients (81.8%) had received high intensity statin therapy for the secondary prevention of the disease. Conclusions: The prevalence of ACS was high between 51-60 years of age, more so in males, smokers, and physically less active patients. Associated comorbidities were hypertension, dyslipidemia and diabetes. Incidence of STEMI was high, and more than half of the patients underwent PCI. Ticagrelor was the most preferred P2Y12 inhibitor in ACS patients for loading as well as maintenance therapy.